BUSINESS STRATEGY FORMULATION - Zafirah, Hana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Competition in the cafe business in Indonesia is getting tougher, including in Malang City. Many coffee shops have sprung up from both large-scale businesses and SMEs underlies the importance of formulating a business development strategy for every cafe business to maintain business sustainability. After 2 years of operating, recently, the XYZ Cafe branch in Malang, has faced shifting in consumer behavior which leads to less optimal strategic planning with recent condition. This serves as a starting point for the research, which attempts to identify both internal and external factors in XYZ Cafe, establish more pertinent strategy formulations, and generate the best possible strategic decisions for business development. This study used a qualitative method with a case study approach. The data sources used were primary data from interviews, as well as secondary data in the form of documents, journals, and so on. The analytical tools used were the IFE-EFE Matrix, SWOT, IE, and QSPM Matrix. The results of the research showed that appropriate strategies are marketing funnel and strategy improvement, then followed by product development and innovation strategy.